2010
DOI: 10.1007/s10484-010-9142-x
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Successful Learning of SMR Neurofeedback in Healthy Participants: Methodological Considerations

Abstract: Neurofeedback (NF) is a tool that has proven helpful in the treatment of various disorders such as epilepsy or attention deficit disorder (ADHD). Depending on the respective application, a high number of training sessions might be necessary before participants can voluntarily modulate the electroencephalographic (EEG) rhythms as instructed. In addition, many individuals never learn to do so despite numerous training sessions. Thus, we are interested in determining whether or not performance during the early tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
74
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(91 citation statements)
references
References 24 publications
10
74
2
Order By: Relevance
“…Furthermore, we found a significant threshold increase after the first session only in SMR NFT group, suggesting that our training protocol is facilitative to golfers. This evidence was in line with previous work in which the SMR amplitude increased above the daily adjusted threshold (Weber, Köberl, Frank, & Doppelmayr, 2011).…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, we found a significant threshold increase after the first session only in SMR NFT group, suggesting that our training protocol is facilitative to golfers. This evidence was in line with previous work in which the SMR amplitude increased above the daily adjusted threshold (Weber, Köberl, Frank, & Doppelmayr, 2011).…”
Section: Discussionsupporting
confidence: 93%
“…Along with an optimistic view on the efficacy of neurofeedback in training the capacity for self regula tion and treating numerous psychosomatic and neuro logical diseases, there are data that the efficiency of α stimulating biofeedback is no higher than 70% [41] or even 50% [6,11,42]. This skepticism has some meth odological grounds: (1) biofeedback training aimed at increasing the power in a standard range not related to individual spectral-frequency characteristics may not only prove ineffective, but even harm the patient's condition [43,44]; (2) some researchers carry out α stimulating training with the subject's eyes open [6,42]; therefore, when teaching the subjects to voluntar ily increase the α wave amplitude with the eyes open, they decrease the degree of activation (the difference between the amplitudes in the eyes closed and eyes open states) [45] and, hence, decrease the subject's capacity for self control [46], which accounts for the low efficiency of α stimulating biofeedback as a self regulation training; (3) the training for an α power increase does not take into account the coherence of the scalp's EMG and EEG signals, which disorient the subjects as to what sensations they should memorize: those corresponding to the α state or to the tension of the scalp muscles [15,16].…”
Section: Discussionmentioning
confidence: 99%
“…Studies examining the effects of NF training on healthy volunteers have also reported that the percentage of individuals who are able to exert control over their EEG is approximately 50 % [75,76]. If only half of children trained with NF are responders, this may account for \the inconsistent results across studies, depending on the composition of the subject group.…”
Section: Responder Statusmentioning
confidence: 99%